Impact of delay in payment, shortage and inflation on an EOQ model with bivariate demand. Issue 2 (3rd April 2021) - Sundararajan, R.; Vaithyasubramanian, S.; Nagarajan, A.
Abstract : The major challenge of inventory decision makers is to determine an inventory optimization strategy that ensures the right balance between keeping abundant on hand inventory to meet the demand of the customers and optimizing costs related to holding inventory. This article analyzes on providing a general deterministic inventory model in which the rate of demand is determined by price and time over the ordering cycle time. The traditional assumption of zero ending invento ry level is relaxed to a non-zero ending inventory level. Shortages are allowed which are partially backlogged. We develop models with partial backlogging and without backlogging. The aim is to maximize the profit per unit time, assuming delay in payment and inflation. An algorithm is proposed to find the optimal selling price, optimal stockout period, optimal replenishment cycle time and the optimal ending inventory level. All the possible special cases of these two models are also discussed. The numerical examples, graphical representation, and sensitivity analysis are given to illustrate the practical application of the proposed model.